(untitled) (Acta Scientiarum. Biological Sciences, 2021)
Streptomyces 5.1 is a bacterium isolated from rice soils in the south of the Tolima department (Colombia). This microorganism is characterized by its antagonistic activity against rubber tree phytopathogens like Colletotrichum gloeosporioides, the causal agent of leaf anthracnose. The antifungal activity of this Streptomyces isolate has been associated with secondary metabolites production. However, the identity of those metabolites is unknown because its purification and identification have not been possible through classic chemical studies. Therefore, aiming to contribute in the study of the secondary metabolites produced by 5.1 from a molecular approach, this research seeks to identify -preliminarily- the genomic fingerprint changes associated with the production of antifungal secondary metabolites produced by Streptomyces 5.1 through the evaluation of a mutant library of 5.1 obtained by random mutagenesis using controlled ultraviolet light exposure. The antifungal activity of obtained mutants was evaluated using Colletotrichum gloeosporioides (C1) fungus as a biosensor, isolated by the Biotechnology Institute of Universidad Nacional de Colombia. In this way, the library of mutants of 5.1, initially formed by 300 isolations, was classified into two phenotypic groups of interest: enhanced mutants (1 isolate) and null mutants (11 isolates) of secondary metabolites. The genomic changes in both groups were analyzed by obtaining the genomic profile of the isolates using Repetitive Extragenic Palindromic (Rep-PCR). The obtained profiles evidenced the presence of one additional band in the enhanced mutant, and the absence of a specific band in the non-producing mutants, both in comparison with the original strain. These bands are proposed for a future sequencing study which will define their role in the production process of metabolites with antifungal activity in Streptomyces 5.1.